1997
DOI: 10.1002/bjs.1800841113
|View full text |Cite
|
Sign up to set email alerts
|

Hand-held Doppler as a screening test in primary varicose veins

Abstract: Hand-held Doppler examination missed LSV or SSV incompetence in 11 per cent of legs, but these included cases with short-duration and low-velocity reflux of dubious clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…Routine preoperative duplex imaging is not advocated in most hospitals because of the perceived marginal benefit and high cost. It has been argued that skilled use of hand‐held Doppler examination obviates the need for duplex ultrasonography12, 14. In a recent study, Smith et al 5 showed that preoperative duplex marking of primary varicose veins did not significantly improve the accuracy or recurrence rate after surgery compared with preoperative examination by hand‐held Doppler testing alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine preoperative duplex imaging is not advocated in most hospitals because of the perceived marginal benefit and high cost. It has been argued that skilled use of hand‐held Doppler examination obviates the need for duplex ultrasonography12, 14. In a recent study, Smith et al 5 showed that preoperative duplex marking of primary varicose veins did not significantly improve the accuracy or recurrence rate after surgery compared with preoperative examination by hand‐held Doppler testing alone.…”
Section: Discussionmentioning
confidence: 99%
“…In most hospitals in Sweden, routine preoperative investigation of patients with primary varicose veins includes inspection, palpation and compression tests, supplemented by hand‐held Doppler testing. Even in skilled hands this may not be sufficient; reflux in the short saphenous vein (SSV) is easily missed, as are anatomical variations and post‐thrombotic changes11–13. In the evaluation of complex peripheral venous disease, traditional non‐invasive tests have been superseded by duplex imaging.…”
Section: Introductionmentioning
confidence: 99%
“… There is a non‐randomized comparative trial comparing the sensitivity and specificity of echography and Doppler auscultation, reporting that no difference was noted in typical cases. Also, as there is a case series study suggesting that the two examinations are similar in sensitivity and specificity, the recommendation level was set at B on the basis of consensus of the committee. The Doppler auscultator (Flow Scope), which is small, light and easy to operate, is a simple and reliable device for the diagnosis of valve insufficiency of superficial veins and is useful for screening . Also, venous ulcers (due to primary or secondary varices) are the most frequent lower leg ulcers, and valve insufficiency of superficial veins can be diagnosed easily and reliably by Doppler auscultation in the standing position (Fig.…”
Section: Cq2: Is Doppler Auscultation Of Superficial Veins Useful Formentioning
confidence: 99%
“…Deshalb bleibt das Verfahren ungenau und ist der farbkodierten Duplexsonographie deutlich unterlegen. Für perfekte Untersucher ist die CW-Dopplersonographie in der Varizendiagnostik einsetzbar (7,12). Refluxphänomene in der V. saphena magna bzw.…”
Section: Résuméunclassified